(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2017)
A person’s knowledge of religion has different understanding levels of. The differences can be caused by various dimensions. Starting from personal experience, normative religious knowledge, as well as religious knowledge historically. When one’s understanding can only rely on one-dimensional understanding, when he/she judges others always assumes those who disagree with him are accused as heresy, and out of the religious rail corridor. To explore the vast ocean of knowledge in religion requires the freedom of the soul, this attitude will lead people beyond the boundaries of the religions. Not only explore the understanding of a religious course, but also be able to explore various cultures and understanding of other religions. Some of them, have dared to explore the limits of inter-religions, where what he got was a ”universal” understanding. Understanding and personal experience that can not be expressed in words. Through the study of religions, we can be find similarities among others. Those are maturity attitude and be able to understand of other religions. In a contras, those whose faith is only based on exoteric understanding only, it means his religion’s understanding or merely on textual religion understanding.